Frequency of Cesarean Section in Patients with Previous One Scar - Asia Asghar, Sadia Habib, Nimra Naeem, Hadia Hussain, Sundus Nawaz, Majida Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of cesarean section in patients with previous one scar. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics and Gynaecology, ATH, Abbottabad from 1st June 2020 to 30th November 2020. Methodology: One hundred and thirty pregnant women with previous one scar were included in the study. All participants were managed as per department protocol and frequency of cesarean section was noted. Results: The age range was from 18 to 35 years with mean age of 29.361±1.95 years, mean gestational age 38.592±1.26 weeks, mean parity 1.923±0.91 and mean weight was 70.776±4.20 kg. Cesarean section was seen in 25.4% patients. Conclusion: Prior scar women are at higher risk of caesarean section unless the type of delivery method. Keywords: Pregnancy, Previous one scar, Cesarean section